Reliability and validation of the Arabic version of the Conditions for Workplace Effectiveness Questionnaire-II - Wafa'a F. Ta'an; Mohammed M. Al-Hammouri; Jehad A. Rababah; Mohammad M. Suliman (Elsevier, 2021)
Objective: This study aimed to examine the psychometric properties of the Conditions for Workplace Effectiveness Questionnaire-II-Arabic Version (CWEQ-II-AV), which measures structural empowerment among nurses. To enhance the usability and credibility of the CWEQ-II among researchers within Arabic-speaking countries, a valid and reliable Arabic version of the measure is necessary. Methods: A cross-sectional research design was used. From December 2018 to June 2019, 275 nurses working in 4 hospitals participated in the study. Reliability was assessed by examining internal consistency and split-half reliability. A confirmatory factor analysis was performed to evaluate the factor structure of the CWEQ-II-AV. Results: The psychometric properties of the CWEQ-II-AV were excellent regarding the six-factor model (opportunity, information, resources, support, formal power, and informal power). The results showed the following fit indices meet the criteria set a priori: comparative fit index (CFI) = 0.96, root mean square of error approximation (RMSEA) = 0.06, and χ2/df = 2.08. Cronbach's α coefficient was 0.95 for the total questionnaire and ranged between 0.83 and 0.89 for the individual subscales. The split-half reliability was 0.91 for the total questionnaire and ranged from 0.83 to 0.87 for individual subscales. Conclusion: This study provides evidence that CWEQ-II-AV is both a reliable and valid measure of structural empowerment among Arab nurses.